Быстродействующий асинхронный электропривод с автономным инвертором тока и активным выпрямителем тока - Волков, Александр Васильевич; Косенко, Игорь Александрович (НТУ "ХПИ", 2010)
By perfection of predicting relay-vector control and reduction of inductance for a smoothing reactor speed of the asynchronous electric drive with current source inverter and current source rectifier is raised. Researches of electromechanical and electromagnetic processes, electromagnetic compatibility of the given electric drive with a mains supply are carried out.
High-speed asynchronous electric drive with current source inverter and current source rectifier
Keywords: электропривод частотно-регулируемый; преобразователь частоты; совместимость электромагнитная; система автоматического управления